PENGARUH HARGA CRUDE PALM OIL (CPO), MINYAK DUNIA DAN FOREIGN DIRECT INVESTMENT (FDI) TERHADAP PERTUMBUHAN EKONOMI DI ASIA TENGGARA DITINJAU DARI PERSPEKTIF EKONOMI SYARIAH - Sulastri, Sri Irma; Andika, Sandi (Relawan Jurnal Indonesia, 2023)
Economic growth in a country is an important aspect of economic development. International trade (export-import) such as crude palm oil, world crude oil and investment such as foreign direct investment is one of the factors that affect economic growth in a country. This study aims to determine and analyze the effect of crude palm oil (CPO) prices, world oil and foreign direct investment (FDI) on economic growth in Southeast Asia from an Islamic economic perspective. The method used is descriptive quantitative. The population is 10 countries in Southeast Asia, the sample in this study uses a purposive sampling technique, the sample is 5 countries which include Malaysia, the Philippines, Cambodia, Singapore and Indonesia with a period of 6 years from 2016-2021. The data analysis method uses panel data regression with 3 approaches to model selection, namely the Chow test, Hausman test and Langrange multiplier test which produces a random effect model (REM). The output results of the REM model show that among the five sample countries the most influential country on economic growth in ASEAN is Indonesia with an equation value of 9.29. The results of the study partially show that the CPO variable with a t-count value of 0.776 > t-table -1.705, then the WTI variable with a t-count value of 2.244 > t-table -1.705 and the FDI variable with a t-count value of 0.272 > t-table -1.705 which states that these three variables have a positive and significant effect on economic growth. Simultaneously, an f-count value of 3.665 > f-table 0.015 is obtained, which means that the independent variables (CPO, WTI, FDI) together have a significant effect on the dependent variable, namely economic growth. The coefficient of determination (R2) shows that CPO, WTI and FDI are able to contribute 21.6%.